Microcatheter Originating Debris during Neuroendovascular Procedures: Mechanism of Dislodgement and Its Prevention - Kan, I.; Karagiozov, K.; Ito, S.; Sato, S.; Murayama, Y. (American Journal of Neuroradiology, 2020)
SUMMARY: Embolic material dislodgement from microcatheters can potentially induce subclinical brain damage as evidenced by a delayed enhanced or other type of lesions. Some of the most frequently used microcatheters were investigated in vitro in different setups and combinations with different port insertions and rotating hemostatic valves. It was found that side port application increases injury to the catheter surface and debris dislodgement by conflicting with internal ledges in rotating hemostatic valves. This initial observation suggests the need for measures to remove the produced debris during such procedures.DELdelayed enhanced lesionFTIRFourier-transform infraredRHVrotating hemostatic valve